Analysis of plasma metabolic profiling and evaluation of the effect of the intake of Angelica keiskei using metabolomics and lipidomics - Oh, Hyun-A; Lee, Hyunbeom; Park, Soo-yeon; Lim, Yeni; Kwon, Oran; Kim, Ji Yeon; Kim, Donghak; Jung, Byung Hwa (Elsevier BV, 2019)
Ethnopharmacological relevance: Angelica keiskei contains many bioactive components with anti-oxidative and anti-inflammatory effects. It is also effective for the treatment of diabetes mellitus, hypertension, and arteriosclerosis, but the relationships between these effects and the active components in the herb have not been studied. Aim of the study: We aimed to confirm the effects of Angelica keiskei on humans. Materials and methods: A metabolomics and lipidomics study was performed using human plasma samples from 20 subjects after the intake of Angelica keiskei, and the components of Angelica keiskei in the plasma were profiled. UPLC-Orbitrap-MS was used to analyze the plasma and plant extracts, and multivariate analysis and correlation studies between the exogenous components from plant and endogenous metabolite in plasma were performed. Results: The levels of the 14 metabolites including kynurenic acid, prostaglandin El, chenodeoxycholic acid, lysoPC (18:1), lysoPC (18:2), lysoPC (20:3), lysoPC (20:4), lysoPC (22:6), PC (34:1), PC (34:2), PC (38:3), PC (38:4), PC (38:6) and PC (40:7) in the plasma were changed. By monitoring the components originating from Angelica keiskei in plasma, five components including 5-methoxypsoralen, 8-methoxypsoralen, 4-hydroxyderricin, xanthoangelol B and xanthoangelol F were detected and they reduced the levels of bile acids and fatty acids. Conclusions: The levels of the metabolites, including bile acids, amino acids, glycerophospholipids and fatty acids, in the plasma were changed, and 14 significantly changed metabolites were closely related to the preventive effect against liver diseases, type 2 diabetes, anemia, obesity, atherosclerosis, depression and antiinflammatory effects. The five components of Angelica keiskei were related the modulatory activity of reducing the levels of bile acids and fatty acids.